Qur’anic Tadabbur Models for Enhancing Students Character and Spiritual Awareness - Aulia, Muhammad Hizba; Syahidin, Syahidin; Faizin, M. Nur; Ali, Muhamad Mauris Faruqi (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2025)
This article examines the design of the Qur’anic Tadabbur Model to enhance Islamic Religious Education (PAI) through the integration of cognitive, affective, and psychomotor domains. The study aims to develop a conceptual framework for the model, focusing on deep reflection on Qur’anic verses to strengthen students' moral character and spiritual awareness. Using a qualitative approach and library research method, the study explores the model's design and its implications for PAI. The findings show that the Qur’anic Tadabbur Model provides a comprehensive approach to fostering students' moral and spiritual development, encouraging reflection on and internalization of Qur’anic values. It not only enhances students' understanding of the Quran but also supports the application of these values in everyday life. Although still in the conceptual stage, further empirical research is required to assess the model's practical effectiveness. These findings lay the foundation for future studies on the implementation of the Qur’anic Tadabbur Model in PAI and its impact on character development.